The Effect of Five Finger Hypnosis Therapy in Reducing Anxiety in Gravida Mothers: Literature Review - Sapiyah Emilinda; Anisa Fitri Rahmawati (PT. Griya Eka Sejahtera, 2021)
Background: Pregnant women often feel worried, afraid or anxious both in primi gravida and multigravida. In primi gravida mothers this feeling of anxiety arises because they have never experienced this process before and in multigravida mothers anxiety usually arises because they think about whether later after delivery they can divide their time, especially in taking care of their children. This study aimed to determine the Effect of Five Finger Hypnosis Therapy in Reducing Anxiety in Mother Gravida. Method: The research design uses a literature review of several research journal articles published on the Health Base. The health databases used include: Google Scholar, and Pubmed with a time span of 2015 to 2020 with search results of 6 journals. The results of this paper indicate that there is an effect of Five Finger Hypnosis Therapy in Reducing Anxiety in Gravida's Mother. Results: Where on average the articles get the results of anxiety before doing finger hypnosis in the mild category, after hypnosis, most of them have mild anxiety levels and there is an influence of hypnosis on anxiety levels in primigravida and multigravida mothers. Conclusion: This five finger hypnosis therapy is very meaningful because with five finger hypnosis therapy pregnant women will get inner peace and relaxation so that the level of anxiety in the mother decreases